MBRS-24. INVESTIGATING THE ROLE OF THE RNA BINDING PROTEIN, MUSASHI 1 IN PEDIATRIC GROUP 3 MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Kameda-Smith, Michelle; Venugopal, Chitra; Bakhshinyan, David; Manoranjan, Branavan; Adile, Ashley; Subapanditha, Minomi; Fleming, Adam; Hope, Kristen; Singh, Sheila
Abstract: BACKGROUND: Pediatric brain tumours are the leading cause of solid cancer mortality with medulloblastoma (MB) representing the most frequent malignant solid central nervous system (CNS) tumour. To date, most experimental efforts to understand the biological mechanism of solid cancers have been directed towards transcriptional regulatory mechanisms that modulate fate determination in stem and progenitor cells. However, little is known regarding post-transcriptional pathways that contribute to mRNA stability, translation into protein, and functional effects on cell fate. The mRNA binding protein, Musashi (Msi) has been observed to play a crucial role in promoting stem cell self–renewal and is implicated in CNS tumours including glioma and MB with associated poor clinical prognosis. METHODS AND RESULTS: Since increasing brain tumour stem cell or brain tumour-initiating cell (BTIC) frequency is associated with tumor aggressiveness and poor patient outcome, we probed for Msi1 within 251 primary human MBs from four transcriptional databases and 74 NanoString-subgrouped MBs, and found it was enriched in aggressive MB subgroups. Applying gene knockdown and overexpression of Msi1 in Group 3 MB, we have performed in vitro and in vivo assays elucidating how these RNA-binding proteins help to maintain the BTIC state promote an aggressive tumour phenotype. CONCLUSION: Though transcriptional manipulation has uncovered novel druggable targets to treat MB, bench-to-bedside clinical translation of these targets has yet to yield significant patient benefit. For the first time, Msi analysis in MB provides a novel paradigm for treatment of MB through targeting post-transcriptional pathways and regulators.